Radiation dose comparison between V/P-SPECT and CT-angiography in the diagnosis of pulmonary embolism. (September 2016) - Isidoro, J.; Gil, P.; Costa, G.; Pedroso Lima, J.; Caseiro Alves, F.; Ferreira, N.C.
Abstract : Introduction: CT pulmonary angiography (CTPA) has become the preferred diagnostic tool in patients suspected of having pulmonary embolism (PE). Ventilation/perfusion single photon emission computed tomography (V/P-SPECT), despite yields similar diagnostic output, it is left to cases were CTPA is inappropriate. Radiation burden should play an important role in modality selection especially in follow-up studies, young woman and pregnant patients. Purpose: The aim of this study is to compare CTPA versus V/P-SPECT, routine protocols of our institution, regarding radiation dose to the more exposed organs (lung and breast) or the embryo/fetus. Materials and methods: In our institution the CTPA protocol includes contrast media administration and scan parameters: 100 kVp, 700 mA, 0, 5s/rot, pitch 0, 984. In V/P-SPECT protocol: ventilation was performed after inhalation of 99m Tc-Technegas, reaching 30 MBq in the lungs; perfusion was performed after i.v. administration of 60–120 MBq 99m Tc-MAA. Radiation dose to lungs and breast form CTPA was estimated using the "ImPACT CT Patient Dosimetry Calculator", the embryo/fetus dose was estimated for different gestational stages (0–7, 8–12, 13–25 and 26–40 weeks) using the web based calculation tool "COnceptus Dose Estimation" (CODE). V/P-SPECT organs and embryo/fetus doses were estimated based on published dose data normalized to administered activity (mGy/MBq). Results: Embryo/fetus absorbed doses are similar for CTPA and V/P-SPECT. Doses to lungs is 1.7–2.6 and to breast is 25–41 times higher from CTPA compared with V/P-SPECT. Conclusion: For the diagnosis of PE in woman, if both imaging modalities are available, it is recommended to proceed with V/P-SPECT rather than CTPA due to the considerable lower radiation dose to the breast. Disclosure: Authors disclose any relationship that may bias their presentation.